Das Gesetz, das Volk und der König: zum gesellschaftlichen Status und zur Funktion der Gesetze im Pentateuch - Oswald, Wolfgang (Die Welt des Orients, 2014)
The monarchic states of the ancient Near East did not know the idea of law giving. In these societies the king incorporated law, righteousness, public order and peace. Inscriptions such as the “Laws of Hammurapi” were not meant to promulgate law but rather to hail the king for his righteous governance. But what was the function of the laws contained in the Pentateuch? Since there is no king to belaud, their function must be different. Several proposals from Wellhausen to Levinson are discussed, all of which seek to find a “Sitz im Leben” for the Pentateuchal laws in the time of the Israelite and Judean monarchies. None of these proposals can stand up to objections. The Covenant Code and the law of Deuteronomy are neither the law of a king, nor of oppositional groups, nor of a religious community. Rather each of the two is meant to serve as a sort of constitution for a citizen-state like body politic. It is likely that both were effective law in post-monarchic Judah.